STRATEGI PROGRAMMING RRI JAYAPURA & MERAUKE DALAM PENGUATAN NKRI DI WILAYAH PERBATASAN - Christiany Juditha (Jurnal Penelitian Komunikasi dan Opini Publik, 2016)
Abstract- Radio Republik Indonesia (RRI) is a medium for broadcast coverage of strategicinformation to the border areas with neighboring countries. However, many issues that arise in thisarea such as about sovereignty, security, as well as concerns the erosion of a sense of nationalismthat have an impact on the integrity of the Unitary Republic of Indonesia (NKRI). RRI is expected tospearhead the dissemination of information to resolve the issue. The purpose of this study was toobtain an overview of the programming strategy of RRI Jayapura and Merauke in the strengtheningof the NKRI in the border region. This research method is a case study with a qualitative approach.The study concluded that RRI Jayapura and Merauke has developed programs tailored broadcast(compability) with the needs of people in the border region. Both also seek to build habits (habitformation) listeners that there is a program of nationalism that could be heard at certain times. RRIalso remains a source of reliable information society, so as to memaksilkan number of listeners(control of audience flow) is not hard to do. Availability of materials and other resources(conservation of program resources) also remains a part that counts both. Including packedprogram of events that attract and accommodate their interests (bredth of appeal) listeners.Keywords: Strategy programming, RRI, NKRI, border.